2021
DOI: 10.1126/sciadv.abe0395
|View full text |Cite
|
Sign up to set email alerts
|

Experimental quantum conference key agreement

Abstract: Quantum networks will provide multinode entanglement enabling secure communication on a global scale. Traditional quantum communication protocols consume pair-wise entanglement, which is suboptimal for distributed tasks involving more than two users. Here, we demonstrate quantum conference key agreement, a cryptography protocol leveraging multipartite entanglement to efficiently create identical keys between N users with up to N-1 rate advantage in constrained networks. We distribute four-photon Greenberger-Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…A thermalised interacting photon gas [123] may also prove to be a suitable source of genuine multipartite entanglement. Recently, the first quantum CKA protocol has been implemented [124] among four parties. The experiment is based on the multiparty BB84 protocol [65] discussed in Section III A.…”
Section: Discussionmentioning
confidence: 99%
“…A thermalised interacting photon gas [123] may also prove to be a suitable source of genuine multipartite entanglement. Recently, the first quantum CKA protocol has been implemented [124] among four parties. The experiment is based on the multiparty BB84 protocol [65] discussed in Section III A.…”
Section: Discussionmentioning
confidence: 99%
“… As universal hashing is used not only for authentication in QKD but also in other steps in QKD like error correction and privacy amplification [ 7 , 13 , 25 30 ], our constructions and results might lead to improvements in QKD protocols, among other areas. Universal hash functions have been recently used in studying quantum secure direct communication (QSDC) [ 75 ] (see also, [ 76 80 ]), quantum secret sharing (QSS) (either directly [ 81 , 82 ] or via a security proof based on QKD [ 83 ]), quantum conference key agreement (QCKA) [ 84 86 ], and quantum authentication [ 87 89 ]. Therefore, our efficient and secure constructions and results might lead to improvements in these directions as well.…”
Section: Polynomial Hash and Its Variantsmentioning
confidence: 99%
“…Universal hash functions have been recently used in studying quantum secure direct communication (QSDC) [ 75 ] (see also, [ 76 80 ]), quantum secret sharing (QSS) (either directly [ 81 , 82 ] or via a security proof based on QKD [ 83 ]), quantum conference key agreement (QCKA) [ 84 86 ], and quantum authentication [ 87 89 ]. Therefore, our efficient and secure constructions and results might lead to improvements in these directions as well.…”
Section: Polynomial Hash and Its Variantsmentioning
confidence: 99%
“…Quantum conference key agreement (QCKA) protocols are designed to allow multiple parties to establish a common, shared, secret key secure against computationally unbounded adversaries. Starting from early work in this field [4,5], QCKA protocols have advanced substantially with new protocols and security proofs [6,7,8]; it is also experimentally feasible [9]. Interestingly, it has been shown that there are some scenarios where such multiparty protocols hold an advantage over the naive use of multiple two-party protocols run in parallel [5].…”
Section: Introductionmentioning
confidence: 99%